Managerial economics : - McGuigan, James R. (Thomson Learrning, 2005)
This book seeks to train learners to think analytically in a business context. Specifically, it uses over 250 real-world,managerially-oriented applications to show readers how managers apply theories and techniques to solve real-world business problems. The book includes extensive coverage of the latest analytical tools in managerial economics: game-theoretic tactics, best-practices mechanismdesign, information economics, and organizational architecture, as well as a thorough integration of international issues.